Virtual reality adoption in marine ecotourism: integrating the health belief model, attitude and eTrust theories - Tan, Hazel Luan Yi (Nanyang Technological University, 2022)
Initiatives for marine conservation are funded by revenue from marine sites. However, the emergence of COVID-19 has restricted travelling, thus leading to decreased revenue and weakening conservation efforts. Virtual reality technology to support marine conservation efforts is explored as it allows users to experience marine sites, without having to be there physically. This study examines factors influencing users’ desire to adopt Virtual Reality Technology in Marine Ecotourism (VRTME). With the integration of Stimulus-Organism-Response (SOR) framework and three behavioural theories (i.e. health belief model, attitude, and eTrust), a hypothetical model was constructed to investigate consumers’ intention to adopt VRTME amidst the pandemic. The data were analysed and interpreted using structural equation modelling after 451 survey responses were obtained via an online questionnaire. Outcome expectation, perceived susceptibility, perceived severity, self-efficacy, and cues to action exhibit significant positive effects on attitude towards VRTME. Consequently, attitude has a direct and indirect influence on use intention via eTrust. Post hoc analysis revealed that self-efficacy has a direct impact on eTrust and use intention. Total effect analysis further concluded that attitude has the greatest influence on use intention of VRTME. This research contributes to the existing literature by utilising health belief factors to explain use intention of technology towards marine conservation efforts. Recommendations including policy formulation and marketing initiatives were generated for marine ecotourism operators and policymakers.